Silicone Oil Droplets in Vitreous after Intravitreal Bevacizumab Injection - Sana Jahangir, Suhail Sarwar, Haroon Tayyab, Asad Aslam Khan Muhammad Ali A Sadiq (Pakistan journal of ophthalmolog (Norton, Va.), 2019)
Intravitreal injection of Bevacizumab for various retinal vascular disorders has become the mainstay of treatment. The injection of Bevacizumab is usually dispensed through local pharmacies after formulating from a larger vial under sterile conditions. We report an interesting finding of silicone oil bubble in vitreal cavity after intravitreal Bevacizumab injection. This is attributed to the fact that the syringes used for dispensing bevacizumab are coated with silicone oil that acts as a lubricant. These silicone oil droplets can lead to floaters and other possible complications. We report two cases of such occurrence and propose strategies to avoid this complication. Keywords: Bevacizumab, diabetic macular edema, silicone oil, ranibizumab.